An outbreak of acute infectious bursal disease in poultry: ultrastructural studies on bursae from clinical cases - CHRISTOPHER, D SURESH; MATHAN, MINNIE; PETER, A B; ANBUMANI, S P; DORAISWAMI, J; RAJENDRAN, M P; MURUGAN, M (The Indian Journal of Animal Sciences, 2013)
Ultrathin sections of bursae from chicks affected with infectious bursal disease (IBD) were studied under transmission electron microscope (TEM). Crystalline array of viral particles in the cytoplasm of mononuclear cells, intracellular oedema, fatty degeneration and marginization of chromatin material were frequently observed. Icosahedral viral particles were seen either free or bound inside phagolysosomes.